Embodiment of rules in action :|primacy of action in late Wittgenstein and Marx - Bakır, Onur. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2010., 2010)
This thesis investigates how rules and actions can be related to each other in an immanent way. To do this, I first focus on a prominent thinker, Ferdinand de Saussure, who defends the inevitability of separating rules and actions fkom each other and of thinking them dichotomously related. We look how he legitimizes and justifies his claim. After showing that the justification process of separation can be explained with the Marxist concept of reification, we look for the possibility of nonreified rule, which does not work in the framework of dichotomy in the texts of Wittgenstein and Marx. I determine the conditions of this type of immanent relation between rules and actions as the primacy of action, the function of rules as embedded grounds in action and the social aspect of any rule governed act. In the next section, I argue that the intimate relation, which is explained as the embodiment of rules in actions, does not raze the differences between rules and actions, and does not misplace the normative character of rules. To do this, I explain how rules and actions, that are co-immanent to each other, influence each other reciprocally and condition each other. In the last chapter, I discuss how this new relationship affects the intellectual practice, and conclude the discussion by synthesizing Wittgenstein's and Marx's two different suggestions, i.e. "to change the world" and "leaving the world as it is."
Keywords: Philosophers -- Germany..